Mobile Information Breastfeeding Model (MIB-Model) On Behaviors and Self-Efficacy of Breastfeeding Among Mothers - Susanti; Rasipin Rasipin; Sutopo Patriajati (Alta Dharma Publisher, 2020)
Breastfeeding is proven to have long-term health benefits for both mothers and infants. The advancement of mobile technology is very useful in promoting health that can change health behaviors. The success of breast milk is not separated from the methods and media used. The study aimed to develop MIB-Model and to examine the effect of MIB-Model on behavior and self-efficacy of breastfeeding among mothers in providing breast milk. The application development method with the software development Live cycle (SDLC) with the waterfall model. The test model is conducted with Quasi-experiment with pre-test, post-test, and control group design. The number of respondents in this study amounted to 40 0rang, 20 for the experimental group, and 20 for the control group. MIB-Model proved its worth having performed with the ISO 9126 standard and can improve knowledge, attitudes, actions, and the baby's weight to the P-value <0.05. In unpaired data analysis, self-efficacy with P-value> 0.05 showed no differences between the intervention and control, support, and experience of being part of self-efficacy formation. MIB-Model is feasible to be utilized and improved primiparous breastfeeding mothers' behavior and the baby's weight and does not increase the self-efficacy mother